Distinct timing of neurogenesis of ipsilateral and contralateral retinal ganglion cells - Marcucci, Florencia (J Comp Neurol, 2018)
In higher vertebrates, the circuit formed by retinal ganglion cells (RGCs) projecting ipsilaterally (iRGCs) or contralaterally (cRGCs) to the brain permits binocular vision and depth perception. iRGCs and cRGCs differ in their position within the retina and in expression of transcription, guidance and activity-related factors. To parse whether these two populations also differ in the timing of their genesis, a feature of distinct neural subtypes and associated projections, we used newer birthdating methods and cell subtype specific markers to determine birthdate and cell cycle exit more precisely than previously. In the ventrotemporal (VT) retina, i- and cRGCs intermingle and neurogenesis in this zone lags behind RGC production in the rest of the retina where only cRGCs are positioned. In addition, within the VT retina, i- and cRGC populations are born at distinct times: neurogenesis of iRGCs surges at E13, and cRGCs arise as early as E14, not later in embryogenesis as reported. Moreover, in the ventral ciliary margin zone (CMZ), which contains progenitors that give rise to some iRGCs in ventral neural retina (Marcucci et al., 2016), cell cycle exit is slower than in other retinal regions in which progenitors give rise only to cRGCs. Further, when the cell cycle regulator Cyclin D2 is missing, cell cycle length in the CMZ is further reduced, mirroring the reduction of both i- and cRGCs in the Cyclin D2 mutant. These results strengthen the view that differential regulation of cell cycle dynamics at the progenitor level is associated with specific RGC fates and laterality of axonal projection.